A correlational study between creative thinking ability and the performance of open-ended science investigations for secondary two female students - Md. Shahrin K.S. Moorthy. (2008)
The call to teach higher-order thinking skills has prompted science educators to seek new strategies in their instructional programme. One suggested strategy is open-ended science investigations. This study explores the relationship between one of the higher-order thinking skills, creativity, and the performance of open-ended science investigations. Specifically, the study seeks to determine the correlation between creative thinking ability and performance of open-ended investigation, as well as each of its six components (preliminary trials, planning, performing, communicating, interpreting and feedback). The study was conducted with only secondary two female students as the researcher intended to use the findings in his current assignment in an all-girls Independent school.